Afrocentricism and resistance in roots: a synergy of counter- hegemonic thrust (2013)
Roots, by Alex Haley, one of the most famous African American slave narratives, has, over time, been critiqued more as a historical text than a literary and creative extension of the African American people. In addition, the tenet of Afrocentricism in the novel has been grossly misrepresented. This research examines the inherent exegesis of Afrocentricism vis-a-vis the notion of Resistance, which constitutes a core thematic preoccupation in the novel and which expurgates the nuances of extremist Afrocentricism. Premised on two sub-tenets of postcolonialism, Afrocentricism and Resistance, this study addresses the complexity of identity construction in the novel. It demonstrates that Afrocentricism and Resistance foreground the sure-fire import of Roots among other collective bodies of African American literature that aply respond to die theme of slavery, its aftermaths, and identity reconstruction. It reaffirms the position of Roots as a canonical literary text whiichi also explicitly projects the tune of liberal Afrocentrism as a crucial step towards identity reconstruction among Africans and people from African descent; the debate of liberal Afrocentricism as a viable roadmap to self-discovery’ among people of African descent; and a physical and psychological rebirth that accentuates the success tale of African American people. It contends that the total emancipation of the African and African American societies lies mainly in the consistent search for both individual and collective identity through a continuous introspect into their past. It concludes that liberal Afrocentricism remains the rational roadmap to understanding Roots, against the backdrop of critics that have misrepresented as well as undermined the legendary import of the novel as a classic African American literan canon.